IMPLEMENTASI MANAJEMEN PENDIDIKAN PADA LINGKUP PROGRAM PEMBELAJARAN DALAM RANGKA PENYELENGGARAAN KELOMPOK BERMAIN YANG BERKUALITASDI KELOMPOK BERMAIN AL AZHAR JAMBI - Kasiono . (Universitas Batanghari Jambi, 2017)
Abstract: The aim of the research is to know the implementation of education management at Al Azhar Play Group. This research is descriptive. The data were obtained by interviewing the Principal, teacher, and administration staff.The results show that there are ten activities of learning program scope management done by institution members. They are: making a yearly working program, making an education calendar, scheduling the learning activities, planning the learning activities, arranging the opening of a new academic year, arranging the implementation of learning program activities, arranging the playing activities, arranging the evaluation of learning program implementation,implementing the guidance and counseling, and arranging the closing of academic year. It can be concluded that if the curriculum or learning program, as a part of the education management is implemented well, then the play group management will be quality.Keywords:Educational Management, Learning Program, Playgroup Al Azhar Jambi